1972
DOI: 10.1111/j.1365-2133.1972.tb00307.x
|View full text |Cite
|
Sign up to set email alerts
|

The Control of Epidermal Thickness*

Abstract: Summary.— Epidermal mass (thickness) is controlled by a complex mechanism in which the epidermal chalone plays a central role. The chalone inhibits epidermal mitotic activity by reducing the proportion of the basal cells that are in the mitotic cycle and the speed at which this cycle is completed. It also acts to reduce the speed at which the distal post‐mitotic cells age and die. The response of the epidermal mass (thickness) to a rising mitotic rate (falling chalone concentration) is divisible into 3 separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

1973
1973
1997
1997

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(23 citation statements)
references
References 6 publications
1
21
0
1
Order By: Relevance
“…for maintaining constant thickness of the epidermis [Weiss and Kavanau, 1957;Iversen, 1961Iversen, , 1969Mercer, 1962;Bullough, 1972]. Chalones, stress hormones (glucocorticoids, catecholamines) and the cyclic AMP/GMP system play an important part in the control of epidermal cell proliferation [Houck and Daugherty, 1974;Voorhees et al, 1976;Wilson and Marks, 1976].…”
mentioning
confidence: 99%
“…for maintaining constant thickness of the epidermis [Weiss and Kavanau, 1957;Iversen, 1961Iversen, , 1969Mercer, 1962;Bullough, 1972]. Chalones, stress hormones (glucocorticoids, catecholamines) and the cyclic AMP/GMP system play an important part in the control of epidermal cell proliferation [Houck and Daugherty, 1974;Voorhees et al, 1976;Wilson and Marks, 1976].…”
mentioning
confidence: 99%
“…The greater activity in the region of the first 100 basal cells indicates that a true increase in mitosis is present at the ulcer edge, a situation which would be compatible with a persisting low local concentration of mitotic inhibitor or chalone due to the unepithelialized area (Bullough, 1973). The increase in epidermal thickness at the ulcer edge is further evidence for an increase in mitosis since in human epidermis increase in mitosis is associated with increase in epidermal thickness (Bullough, 1972). If epidermal cells are still being produced at the margins of non-healing lesions, the lack of production of new cells would not appear to be the reason for the failure of epithelialization, and there must be some other fundamental cause such as failure of cells to adhere to one another or their substrate.…”
Section: Mitotic Activitymentioning
confidence: 95%
“…Collagen and hence skin thickness and firmness are reduced by the inhibitive action of glucocor ticoids on fibroblast, fibrin, and exudate for mation [A!rich et ah, 1951;Spain and Molomut, 1952;Perasalo et ah, 1953; also, long bone cortical thickness is reduced in heat-and cold-exposed rats and mice; Riesenfeld, 1976;Brandt and Siegel, 1978]. Bullough [1972] has also shown that reduction of skin thickness may be due to the interaction of glucocorticoids and epi dermal chalone, resulting in decreased mito tic efficiency.…”
Section: Discussionmentioning
confidence: 99%